Comparative analysis of cancer statistics in China and the United States in 2024 - Yujie Wu; Siyi He; Mengdi Cao; Yi Teng; Qianru Li; Nuopei Tan; Jiachen Wang; Tingting Zuo; Tianyi Li; Yuanjie Zheng; Changfa Xia; Wanqing Chen; et al. (Chinese Medical Journal)
Abstract. Background:. Cancer patterns in China are becoming similar to those in the United States (US). Comparing the recent cancer profiles, trends, and determinants in China and the US can provide useful reference data. Methods:. This study used open-source data. We used GLOBOCAN 2022 cancer estimates and United Nations population estimates to calculate cancer cases and deaths in both countries during 2024. Data on cancer incidence and mortality trends were obtained from the Surveillance, Epidemiology, and End Results (SEER) program and National Centre for Health Statistics in the US and cancer registry reports of the National Cancer Center (NCC) of China. Data from the Global Burden of Disease study (GBD) and a decomposition approach were used to estimate the contributions of four determinants to the change in cancer deaths. Results:. In 2024, there are an estimated 3,246,625 and 2,510,597 new cancer cases and 1,699,066 and 640,038 cancer deaths in China and the US, respectively. The highest estimated cancer cases are lung cancer in China and breast cancer in the US. The age-standardized incidence rates of lung and colorectal cancer in the US, and stomach, liver, and esophageal cancer in China have decreased, but the incidence rates of liver cancer in the US and colorectal cancer, prostate cancer in men, and cervical cancer in women in China have increased. Increases in the adult population size and population aging are main reasons for the increase in cancer deaths; case fatality rates are a main reason for the decrease in cancer deaths in both countries. Conclusions:. China has made progress in cancer control but lags the US. Considering the transformation in China’s pattern of cancers epidemiology, it is imperative to develop stronger policies by adopting the cancer prevention and control strategies used in the US to address population aging and curb growing cancer trends.